$ {2}^{1-1/x}=\sqrt[x]{3^x+1}/9 $

I tried to solve this equation using Logarithms:

$ \log_2 {2}^{(x-1)/x}=\log_2 \sqrt[x]{3^x+1}/9 $


$ (x-1)/x=\log_2 \sqrt[x]{3^x+1}/9 $

from here I don't know what to do as for the second logarithm I don't know how to extract the exponent.

  • $\begingroup$ Do you mean $$9\cdot 2^{1-\frac{1}{x}}=(3^x+1)^{1/x}$$? $\endgroup$ – Dr. Sonnhard Graubner Nov 4 '18 at 17:58
  • $\begingroup$ A few logarithm properties that might help somehow. Something to play around with in any event. $$log_a(b^n) = n \cdot log_a(b)$$ $$log_a(b/c) = log_a(b) - log_a(c)$$ $\endgroup$ – Eevee Trainer Nov 4 '18 at 17:59
  • $\begingroup$ ok so $ \log_2 \frac{{2}^{(x-1)/x}}{\sqrt[x]{3^x+1}/9} $ $\endgroup$ – Norman Facco Nov 4 '18 at 18:08
  • $\begingroup$ I don't see an obvious solution of the equation. Are you sure it's $3^x+1$? Shouldn't it read $3^{x+1}$? In the latter case the equation is easy to solve. $\endgroup$ – Michael Hoppe Nov 4 '18 at 18:11
  • $\begingroup$ yes Dr. Sonnhard Graubner, I mean that. $\endgroup$ – Norman Facco Nov 4 '18 at 18:11

There isn’t a good way to solve this. Always recall the following properties of logarithms when attempting to solve equations. (These are some of the important ones.)

$$\log a+\log b = \log (ab)$$

$$\log a-\log b = \log \frac{a}{b}$$

$$\log a^b = b\log a$$

$$\log_{a^b} c = \frac{1}{b} \log c$$

$$\log_a a = 1$$

$$\log_a b = \frac{1}{\log_b a}$$

Using these properties, it becomes apparent that the equation can’t be solved normally.

$${2}^{1-\frac{1}{x}} = \frac{\sqrt[x]{3^x+1}}{9}$$

$$9\cdot {2}^{1-\frac{1}{x}} = \sqrt[x]{3^x+1}$$

$$\ln \big(9\cdot {2}^{1-\frac{1}{x}}\big) = \ln \sqrt[x]{3^x+1}$$

$$\ln \big(9\cdot {2}^{1-\frac{1}{x}}\big) = \ln ({3^x+1})^{\frac{1}{x}}$$

$$\ln 9+\ln {2}^{1-\frac{1}{x}} = \ln ({3^x+1})^{\frac{1}{x}}$$

$$\ln 9+\big(1-\frac{1}{x}\big)\ln {2} = \frac{1}{x} \ln ({3^x+1})$$

$$\ln 9+\ln 2-\frac{1}{x}\ln 2 = \frac{1}{x} \ln ({3^x+1})$$

Had the question had $3^{x+1}$, you would use the property $\log a^b = b\log a$. From there, you would isolate $x$-terms on one side and then solve for it. However, there is a sum. Logarithms don’t work well with those.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.